Moving Memory: The Buildings of the Warburg Institute - Tim Ainsworth Anstey (Kunst og Kultur)
When the Warburg Institute was transferred from Hamburg to London in 1933 its scholars were equipped with strong image-experiences of architectural design. This article tells the story of how continuity and memory were created through the Warburg Institute’s ensuing projects of architectural commissioning, addressing particularly the agency of one individual, Gertrud Bing, who as assistant librarian of the Warburg Institute participated in the design of its first building and who as Director oversaw the development of its last.